P103 Increasing STI diagnosis, treatment and awareness at the world's largest annual sexuality and lifestyle convention with the aid of point-of-care testing. (30th June 2016) - Turner, Rosemarie; Day, Sara; Allen, Katie; Ostridge, Emma; Nulty, Kate; Cooney, Grainne; Hardie, James; Payne, David; Svensson, Ella; Lampejo, Temi
Abstract : Background: Sexpo is the largest sexual health and lifestyle exhibition in the world. It launched in the UK (London) in November 2015. Aim: Raise sexual health awareness and offer STI screening to attendees identifying whether these clients attend mainstream GUM services. Methods: A health bus was stationed inside the exhibition where attendees and exhibitors received a sexual health consultation and free STI testing (including HIV point of care tests), condoms and contraceptive information. Interactive seminars, covering common sexual health and contraceptive themes, were delivered by our team of five nurses, two health advisers, one doctor and one event co-ordinator. Results: 205 patient consultations occurred. These were 56% (114) male, 44% (89) female and a median age 33 years. Most clients were white British, 51% (104), or white Other, 23% (47). 77% (156) identified as heterosexual, 10.8% (22) bisexual women, 9.9% (20) MSM, 0.5% (1) WSW and 2% (4) declined to answer. 5% (12) identified as swingers. 100% were offered an HIV test, 188 (94%) accepted. 31.5% (64) clients had never tested for HIV before. 199 clients accepted either HIV or STI testing: of these 5% (10) were diagnosed with an STI. All patients with an STI were offered treatment. 3% (6) clients reported hazardous use of drugs. Discussion: Visitors to this exhibition found our opportunistic sexual health screening acceptable. Up to 15% of our clients were amongst high risk groups and 1 in 20 clients were diagnosed with an STI. 31.5% (64) clients had not accessed mainstream GUM services before.